The Impact of Social Media, Customer Experience and Servicescape on The Revisit Intention in Marine Tourism (A Case Study on Akkarena Beach, Makassar) - Adam Andy Omar, Yaumil Atia; Amri, Andi; Hasani, M. Chasyim (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2021)
This study aims to determine the impact of social media, customer experience and servicescape on revisit intention in marine tourism objects at Akkarena Beach, Makassar and to determine the factors that impact the interest in revisit intention to Akkarena Beach, Makassar. This research was conducted from January to March 2021. The type of research used is associative. The research data was collected using the interview method and the distribution of a list of questions (questionnaires) distributed to 94 respondents who had visited the Akkarena Beach marine tourism object and active users of social media. The analysis technique used is multiple regression to prove the research hypothesis. Data that has met the validity test, reliability test and classical assumption are the processed to obtain a regression equation. The results of this research indicate that the impact of social media, customer experience and servicescape together has a positive and significant effect on revisit intention with a value of Fcount 11,403 > Ftable 2,709. The partial test shows that social media, customer experience and servicescape each have a positive and significant effect on revisit intention. Social media variabels have a positive and significant effect on revisit intention, it is seen from the value of Tcount 2,893 > Ttable 1,9864 with significance 0,002 < 0,05. Customer experience variabels have a positive and significant effect on revisit intention, it is seen from the value of Tcount 4,038 > Ttable 1,9864 with a significance 0,000 < 0,05. Servicescape variabels have a positive and significant effect on revisit intention, it is seen from the value of Tcount 2,984 > Ttable 1,9864 with a significance 0,004 < 0,05. The value of Adjusted R Square obtained from the Determinant Coefficient (R2) test on the revisit intention of 0,651 explains that 65,1% in revisit intention is able to be explained by variables are social media, customer experience and servicescape, while the remaining 34,9% us explained by other variables that are not investigated in this research.